2015
DOI: 10.1089/bfm.2014.0138
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Outcomes of Extremely Low Birth Weight Infants After Introduction of Donor Milk to Supplement Mother's Milk

Abstract: Our results add evidence supporting the safety of donor milk. This study also found an association between exposure to formula in preterm infants and the requirement for respiratory support, a finding that warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 35 publications
0
52
0
Order By: Relevance
“…Lactoferrin has been found to mitigate the release of proinflammatory cytokines from monocytic cells in the presence of lipopolysaccharides (11). Breast milk also contains a host of immune cells such as mucosal-protective IgA; growth factors to promote enterocyte development; a phospholipid mediator, platelet-activating factor acetylhydrolase, which may be protective against NEC; Igs, cytokines, chemokines, prostaglandins, neuropeptides, and nucleotides; an appropriate pH and osmolarity for a newborn's naïve gut; microbiota to colonize the gut and establish a healthy mucosal layer; and probiotic human milk oligosaccharides to facilitate the colonization of beneficial bacteria such as Lactobacillus and Bifidobacterium (7,64,65). Together, these active breast milk components promote the proliferation of beneficial microbiota relative to enterobacteria and influence immune system responses to favor an anti-inflammatory environment that is suspected to be protective against NEC and other diseases (26,33).…”
Section: Sources Of Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactoferrin has been found to mitigate the release of proinflammatory cytokines from monocytic cells in the presence of lipopolysaccharides (11). Breast milk also contains a host of immune cells such as mucosal-protective IgA; growth factors to promote enterocyte development; a phospholipid mediator, platelet-activating factor acetylhydrolase, which may be protective against NEC; Igs, cytokines, chemokines, prostaglandins, neuropeptides, and nucleotides; an appropriate pH and osmolarity for a newborn's naïve gut; microbiota to colonize the gut and establish a healthy mucosal layer; and probiotic human milk oligosaccharides to facilitate the colonization of beneficial bacteria such as Lactobacillus and Bifidobacterium (7,64,65). Together, these active breast milk components promote the proliferation of beneficial microbiota relative to enterobacteria and influence immune system responses to favor an anti-inflammatory environment that is suspected to be protective against NEC and other diseases (26,33).…”
Section: Sources Of Nutritionmentioning
confidence: 99%
“…A recent Japanese study found that the odds of mortality increase as the SD for birth weight decreases for growth-restricted extremely preterm infants (6). LBW (1500-2499 g), very low birth weight (VLBW) (1000-1499 g), and extremely low birth weight (<1000 g) have been linked to several morbidities, including chronic lung disease, retinopathy of prematurity, sepsis, and necrotizing enterocolitis (NEC) (1,(6)(7)(8). Preventing and ameliorating the effects of these morbidities is an ongoing challenge in neonatology.…”
Section: Introductionmentioning
confidence: 99%
“…Quigley et al point out that all but one of the randomized controlled trials examined in their meta-analysis were >25 years old, when smaller VLBW infants did not survive, and these studies also may not be reflective of current practice [44]. In a more recent study conducted in 2012–2014, The Early Nutrition Study Randomized Clinical Trial found no difference in infections, necrotizing enterocolitis, or mortality during the first 60 days of life in 373 infants fed pasteurized donor milk or preterm formula for supplemental feedings [48]. Another study 2014 of 201 ELBW infants found no difference in NEC or infection rates between infants receiving human milk (including donor milk) and infants receiving formula; however, the duration of mechanical ventilation was significantly higher among formula-fed infants (24 vs. 60 h, p = 0.016) in the group exposed to formula [48].…”
Section: Discussionmentioning
confidence: 99%
“…2 We reported no difference in weight or change in weight z-score or rate of SGA from birth to discharge for human milk-fed vs formula fed-infants. 3 Chowning et al 4 report equivalent growth outcomes for infants who received human milk on <50% of hos-pital days and infants who received it $50% of hospital days.…”
Section: Weight Gain and Bronchopulmonary Dysplasia In Human Milk Fedmentioning
confidence: 99%